Clinical Pharmacogenetics Implementation Consortium (CPIC) Guideline for CYP2B6 and Efavirenz‐Containing Antiretroviral Therapy. Issue 4 (5th July 2019) - Desta, Zeruesenay; Gammal, Roseann S.; Gong, Li; Whirl‐Carrillo, Michelle; Gaur, Aditya H.; Sukasem, Chonlaphat; Hockings, Jennifer; Myers, Alan; Swart, Marelize; Tyndale, Rachel F.; Masimirembwa, Collen; Iwuchukwu, Otito F.; et al.
Abstract : The HIV type‐1 nonnucleoside reverse transcriptase inhibitor, efavirenz, is widely used to treat HIV type‐1 infection. Efavirenz is predominantly metabolized into inactive metabolites by cytochrome P450 (CYP)2B6, and patients with certain CYP2B6 genetic variants may be at increased risk for adverse effects, particularly central nervous system toxicity and treatment discontinuation. We summarize the evidence from the literature and provide therapeutic recommendations for efavirenz prescribing based on CYP2B6 genotypes.